(untitled) (University Arena, 2025)
Spontaneous movements represent the first expression of human motor behavior, of the developing central nervous system, reflecting the level of neurological maturation. They have an essential contribution to the organization of neuronal connections and subsequent motor acquisitions. The first movements appear around the 7th week of gestation and are generated by subcortical neural networks. Professor Christa Einspieler (2004) suggests that the first half of pregnancy is a period of learning and development for most fetal movement patterns, and these continue to develop in the second half of pregnancy and after birth. Motor activity develops as an integrated dynamic system, with fetal movements representing the biological and functional basis of human motor function. They are influenced by genetic, biological and sensory factors, essential for the formation of neural pathways and preparation for extrauterine life. According to current studies and theories, early newborn behaviors follow a continuous adaptive pathway similar to the prenatal motor repertoire of the fetus. Widström and Brimdyr (2011) described nine predictable stages of instinctive behaviors observed during the first hour after birth in undisturbed skin-to-skin contact, enhancing bonding, physiological regulation, and breastfeeding. Bergman (2015) highlights that “the newborn’s brain expects to be skin-to-skin after birth,” and that postnatal separation acts as a eurodevelopmental stressor. In preterm infants, this interrupted continuity, abrupt transition to the external environment and an immature nervous system will increase the risk of motor disorders. Dr.Prechtl (2001) stated that “general movements are the most sensitive and specific behavioral markers for predicting later neurological deficits.” From a kinanthropological perspective, these movements are fundamental elements of neuro-motor development, but also early indicators of central nervous system (CNS) maturation. These observations from intrauterine life, but also immediately after birth, may have implications for early assessment and intervention, through the development and application of an integrated model of pediatric kinesiology.